2013
DOI: 10.1093/nar/gkt520
|View full text |Cite
|
Sign up to set email alerts
|

Programmable repression and activation of bacterial gene expression using an engineered CRISPR-Cas system

Abstract: The ability to artificially control transcription is essential both to the study of gene function and to the construction of synthetic gene networks with desired properties. Cas9 is an RNA-guided double-stranded DNA nuclease that participates in the CRISPR-Cas immune defense against prokaryotic viruses. We describe the use of a Cas9 nuclease mutant that retains DNA-binding activity and can be engineered as a programmable transcription repressor by preventing the binding of the RNA polymerase (RNAP) to promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
1,044
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,042 publications
(1,090 citation statements)
references
References 45 publications
40
1,044
0
6
Order By: Relevance
“…When all five fgf8ats-gRNAs were co-injected with dCas9-KRAB mRNA into one-cell stage wild-type fertilized eggs, the resulted embryos showed reduced fgf8a expression at 11 hpf ( Figure 1J and Supplementary information, Figure S1hC) and smaller otic vesicle at 32 hpf (Supplementary information, Figure S1iA-S1iB). Similarly, we observed that foxi1 expression and otic vesicle size were reduced when dCas9-KRAB mRNA and all five foxi1ts-gRNAs (1)(2)(3)(4)(5) were injected ( Figure 1K, Supplementary information, Figure S1hD, S1iA and S1iC). If dCas9-VP160 mRNA and fgf8ats-gRNAs (6-10) or foxi1ts-gRNAs (6-10) were co-injected, an elevated expression of fgf8a or foxi1 was observed ( Figure 1L and 1M and Supplementary information, Figure S1hE and S1hF), leading to enlarged otic vesicles (Supplementary information, Figure S1iD-S1iF), and enhanced fgf8a or foxi1 expression appeared to be near their endogenous expression locations (Supplementary information, Figure S1j).…”
supporting
confidence: 59%
See 3 more Smart Citations
“…When all five fgf8ats-gRNAs were co-injected with dCas9-KRAB mRNA into one-cell stage wild-type fertilized eggs, the resulted embryos showed reduced fgf8a expression at 11 hpf ( Figure 1J and Supplementary information, Figure S1hC) and smaller otic vesicle at 32 hpf (Supplementary information, Figure S1iA-S1iB). Similarly, we observed that foxi1 expression and otic vesicle size were reduced when dCas9-KRAB mRNA and all five foxi1ts-gRNAs (1)(2)(3)(4)(5) were injected ( Figure 1K, Supplementary information, Figure S1hD, S1iA and S1iC). If dCas9-VP160 mRNA and fgf8ats-gRNAs (6-10) or foxi1ts-gRNAs (6-10) were co-injected, an elevated expression of fgf8a or foxi1 was observed ( Figure 1L and 1M and Supplementary information, Figure S1hE and S1hF), leading to enlarged otic vesicles (Supplementary information, Figure S1iD-S1iF), and enhanced fgf8a or foxi1 expression appeared to be near their endogenous expression locations (Supplementary information, Figure S1j).…”
supporting
confidence: 59%
“…CRISPR interference (CRISPRi) is a recently developed tool used to study single guide RNA (gRNA)-mediated sequence-specific repression of transcription in both prokaryotic and eukaryotic cells [1][2][3][4][5]. Transcription initiation and elongation of a gene can be interfered by the presence of gRNA:DNA hetero-duplex/dCas9 (a catalytically inactive form of Cas9) complex in its promoter and exons.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Interference results from a corresponding transcript that is processed selectively at each repeat sequence, forming CRISPR RNAs (crRNAs) that guide Cas proteins for sequence-specific recognition and cleavage of target DNA complementary to the spacer (7). CRISPR-Cas technology has applications in strain typing and detection (8)(9)(10), exploitation of natural/engineered immunity against mobile genetic elements (11), programmable genome editing in diverse backgrounds (12), transcriptional control (13,14), and manipulation of microbial populations in defined consortia (15).…”
mentioning
confidence: 99%